Exploring Students’ Creative Thinking in Mathematical Problem Solving: A Descriptive Qualitative Study - Hilda Mahmudah; Mohamad Gilar Jatisunda (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
This study explores students’ creative thinking skills in mathematics through a descriptive qualitative approach. The purpose of the research is to examine how students construct and express original ideas when solving open-ended mathematical problems. Participants were selected purposively based on their prior experience with similar tasks, and data were obtained from students’ written responses to problem-solving activities designed to promote divergent thinking. These tasks emphasized multiple solution strategies, reasoning justification, and reflection on originality. The data were analyzed thematically using NVivo 14, focusing on creativity indicators such as fluency, flexibility, originality, and elaboration. The findings indicate that some students were able to demonstrate creative approaches in generating diverse and original solutions, while others experienced difficulties due to limited conceptual understanding and time constraints. These results underscore the need for instructional practices that strengthen prerequisite knowledge, offer varied task designs, and allocate sufficient time to enhance students’ mathematical creativity. Overall, the study contributes to the development of pedagogical strategies that foster creative problem-solving in mathematics classrooms.